Knowledge Management dan Knowledge Sharing Terhadap Kinerja Pegawai Dengan Individual Innovation Capability - Regi julianda; Vicky Brama Kumbara; Desi Permata Sari (Jurnal Ekonomi dan Bisnis Digital, 2026)
This study aims to analyze the influence of Knowledge Management and Knowledge Sharing on Employee Performance, with Individual Innovation Capability as an intervening variable at the High Prosecutor's Office of West Sumatra. The method used in this research is quantitative, with a total of 60 respondents. The data analysis technique employed is Structural Equation Modeling (SEM) using SmartPLS. Data collection was conducted through the distribution of questionnaires designed using a Likert scale. The results of the study show that there is a negative and insignificant influence of Knowledge Management on Individual Innovation Capability. There is a positive and significant influence of Knowledge Sharing on Individual Innovation Capability. There is a negative and insignificant influence of Knowledge Management on Employee Performance. There is a positive and significant influence of Knowledge Sharing on Employee Performance. There is a positive and significant influence of Individual Innovation Capability on Employee Performance. Furthermore, the mediation test results indicate that Individual Innovation Capability is able to mediate the influence of Knowledge Sharing on Employee Performance.